Leadership Development of Rehabilitation Professionals in a Low-Resource Country: A Transformational Leadership, Project-Based Model - Pascal, Maureen Romanow; Mann, Monika; Dunleavy, Kim; Chevan, Julia; Kirenga, Liliane; Nuhu, Assuman (Frontiers in Public Health, 2017)
Background and rationale This paper presents an overview of the activities and outcomes of the Leadership Institute (LI), a short-term leadership development professional development course offered to physiotherapists in a low-resource country. Previous studies have provided examples of the benefits of such programs in medicine and nursing, but this has yet to be documented in the rehabilitation literature. The prototype of leadership development presented may provide guidance for similar trainings in other low-resource countries and offer the rehabilitation community an opportunity to build on the model to construct a research agenda around rehabilitation leadership development. Pedagogy The course used a constructivist approach to integrate participants’ experiences, background, beliefs, and prior knowledge into the content. Transformational leadership development theory was emphasized with the generation of active learning projects, a key component of the training. Outcomes Positive changes after the course included an increase in the number of community outreach activities completed by participants and increased involvement with their professional organization. Thirteen leadership projects were proposed and presented. Discussion The LI provided present and future leaders throughout Rwanda with exposure to transformative leadership concepts and offered them the opportunity to work together on projects that enhanced their profession and met the needs of underserved communities. Constraints and challenges Challenges included limited funding for physiotherapy positions allocated to hospitals in Rwanda, particularly in the rural areas. Participants experienced difficulties in carrying out leadership projects without additional funding to support them. Lessons learned While the emphasis on group projects to foster local advocacy and community education is highly recommended, the projects would benefit from a strong long-term mentorship program and further budgeting considerations. Conclusion The LI can serve as a model to develop leadership skills and spur professional growth in low-resource settings. Leadership development is necessary to address worldwide inequities in health care. The LI model presents a method to cultivate transformational leadership and work toward improvements in health care and delivery of service.